A Rapid Biochemical and Radiological Response to the Concomitant Therapy with Temozolomide and Radiotherapy in an Aggressive ACTH Pituitary Adenoma. (5th March 2017) - Misir Krpan, Ana; Dusek, Tina; Rakusic, Zoran; Solak, Mirsala; Kraljevic, Ivana; Bisof, Vesna; Ozretic, David; Kastelan, Darko
Abstract : Background and Importance . In the last eight years temozolomide (TMZ) has been used as the last-line treatment modality for aggressive pituitary tumors to be applied after the failure of surgery, medical therapy, and radiotherapy. The objective was to achieve a rapid control of tumor growth and hormone normalization with concurrent chemoradiotherapy in a patient with very aggressive ACTH pituitary adenoma. Clinical Presentation . We describe a patient with an aggressive ACTH-producing adenoma treated with concurrent temozolomide and radiotherapy. The patient suffered from an aggressive ACTH adenoma resistant to surgical and medical treatment. After two months of concurrent temozolomide and radiotherapy, cortisol normalization and significant tumor shrinkage were observed. After 22 months of follow-up, there is still no evidence of tumor recurrence. Conclusion . Concurrent treatment with temozolomide and irradiation appears to be highly effective in the achievement of the tumor volume control as well as in the control of ACTH secretion in aggressive ACTH adenoma.